Trimetazidine has protective effects on spermatogenesis in a streptozotocin-induced diabetic rat model - Ozcan, M. F.; Hekimoglu, Emine Rümeysa; Ener, K.; Namuslu, M.; Altintas, R.; Celik, H. T.; Akbulut, Z.; Altinova, S. (Wiley, 2017)
The aim of this study was to investigate the protective effects of trimetazidine (TMZ), as an antioxidant agent, on streptozotocin (STZ)-induced diabetic rats. A total of 50 male Sprague Dawley rats were randomly classified into five groups as follows: Group 1 (control), Group 2 (STZ-induced diabetic rats), Group 3 (STZ-induced diabetic rats treated orally with 1 cc/day isotonic saline), Group 4 (diabetic rats treated orally with 10 mg/kg/day TMZ) and Group 5 (diabetic rats treated orally with 20 mg/kg/day TMZ). After 8 weeks, orchiectomy was carried out. Histopathological and electron microscopic examinations were performed in all groups. In groups 1 and 5, the structural and ultra-structural findings of the testicular tissue and spermatogenesis were found normal. In groups 2, 3 and 4, similar results were obtained in terms of the impaired testicular architecture and degeneration of spermatogenesis. The administration of an optimal dose of TMZ protects against the harmful effects of diabetes mellitus on spermatogenesis in rats. TMZ therapy can be used to maintain normal spermatogenesis in diabetic rats.
Keywords: Male; Trimetazidine; Protective Agents; Antioxidants; Diabetes Mellitus, Experimental; Rats; Rats, Sprague-Dawley; Testis; diabetes; rats; spermatogenesis; streptozotocin; trimetazidine; Animals; Spermatogenesis; 3. Good health